The Utilization of Digital Media in the English Learning Process: A Study in the Business Administration Department - Reski Amalia S; Mega Fitri Wulandari; Irfiani Bakri; Walangitan Melania Rut (Hasanuddin University, 2025)
The use of digital media in English language learning represents a strategic approach to preparing students for the demands of the professional world, where technology and digital communication are highly prioritized. The integration of digital media enables students to access authentic English learning materials, thereby enhancing their linguistic competence in ways that align with workplace requirements. The urgency of this study lies in the necessity to understand the effectiveness and patterns of digital media utilization in supporting the achievement of English language competencies relevant to the needs of business and industry. The research explored the way digital media applied in English language learning at the Department of Business Administration. It focuses on the types of digital media used, the challenges faced, and the impact on students' English skills. The study employs a qualitative method, incorporating classroom observations and semi-structured interviews with students and lecturers. Purposive sampling was applied. The population includes all students and lecturers in the department. The sample consists of second-semester students from Business Administration (II AB1 and II AB2), Business Management (II MB1–MB5) and seven English lecturers. These research results are expected to give insights for evaluation and decision-making. They will help the Department of Business Administration work towards its goal of developing internationally competitive management professionals.